A Thermally Populated, Perpendicularly Twisted Alkene Triplet Diradical. (20th October 2016) - Wentrup, Curt; Regimbald‐Krnel, Michèle J.; Müller, Dennis; Comba, Peter
Abstract: Variable‐temperature NMR and ESR spectroscopic studies reveal that bis(dibenzo[a, i]fluorenylidene)1 possesses a singlet ground state, 1 (S0 ), while the 90° twisted triplet1 (T1 ) is populated to a small extent already at room temperature. Analysis of the increasing amount of paramagnetic1 (T1 ) at temperatures between 300 and 500 K yields the exchange interaction J ex / h   c =3351 cm −1 and a singlet–triplet energy splitting of 9.6 kcal mol −1, which is in excellent agreement with calculations (9.3 kcal mol −1 at the UKS BP86/B3LYP/revPBE level of theory). In contrast, the zero‐field splitting parameter D is very small (calculated value −0.018 cm −1 ) and unmeasurable.